Awareness as means of achievement of good life by personality - L. Terletska, (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
Research actuality. Today in interpretation of the marked psychological phenomenon the conceptual unity is absent. It's happened because of complication of phenomen of self-awareness and difficulties of generalization and reducing to only denominator of existing in science conceptions of consciousness.A research aim is to determinate the maintenance of concept of good life of personality and the place and role of awareness in the achievement of such life.A term "good life" was introduced by Carl Rogers. It meant as a process of the following a way chosen by human organism, when he has internal freedom for motion in any direction. The basic qualities of this process are universal.To our opinion every personality on the way to good life and psychical health must do a choice: 1) to live, to realize, to open up, to experience, to operate, to create, to unite or 2) to die, not to realize, to unopen up, not to experience, not to operate, to destroy, to mark off. If personality uses the first way she chooses harmony of psychical life, if second way - it is a way to degradation and disintegration of personality.The effects of process of awareness show up in realistic vision of somebody in the own world, in more clear understanding of the motivation and behavior, in a consent and acceptance of feeling of psychical equilibrium, in the increase of love, sense of empathy and kindness.All of it comes forward as the spark of good, mature, psychologically healthy life of personality.
Keywords: good life; psychologically healthy personality; self-awareness